Contractual Price Provisions and Their Determinants in Conditions of Uncertainty: The Case of Chilean Fruit Exports - Pavez, Iciar; Codron, Jean-Marie (Management international / International Management / Gestiòn Internacional, 2018)
This article analyzes the choice of export contracts of perishable goods. It draws on the Transactional Cost Theory, and particularly the literature of incomplete contracts. Using a 2014 database of 177,296 transactions and corresponding contracts performed by Chilean fruit exporters, together with qualitative information gathered from a field survey, we show through a binomial logit that the choice between firm sale and consignment is a function of the environmental uncertainty of the importing country, the temporal specificity of the transacted product and the frequency of transactions.